Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 1/2 + 3/4 - (3/4 - 4 - 5)
= 1/2 + 3/4 - 3/4 + 4 + 5
= (3/4 - 3/4) + (4 + 5) + 1/2
= 0 + 9 + 1/2
= 19/2
b) [9/16 + 8/(-27)] - (19/27- 7/16 - 2)
= 9/16 - 8/27 - 19/27 + 7/16 + 2
= (9/16 + 7/16) + (-8/27 - 19/27) + 2
= 1 - 1 + 2
= 2
c) -5/8 . [4/9 + 7/(-12)]
= -5/8 . (-5/36)
= 25/288
d) 7/10 . (-3/5) + 7/10 . (-2/5) - (-3/10)
= 7/10 . (-3/5 - 2/5) + 3/10
= 7/10 . (-1) + 3/10
= -2/5
e) -3/7 . 5/9 + 4/9 . (-3/7) + 2 3/7
= -3/7 . (5/9 + 4/9) + 17/7
= -3/7 . 1 + 17/7
= 2
f) 8 2/7 - (3 4/9 + 4 2/7)
= 8 + 2/7 - 3 - 4/9 - 4 - 2/7
= (8 - 3 - 4) + (2/7 - 2/7) - 4/9
= 1 - 4/9
= 5/9
h) 3.(-1/2)² - (4/5 + 8/15) : 5/6
= 3.1/4 - 4/3 : 5/6
= 3/4 - 8/5
= -17/20
![](https://rs.olm.vn/images/avt/0.png?1311)
a) =\(\left[\left(12+1\right)^2+\left(12+2\right)^2\right]:\left(13^2+14^2\right)\)
=1
b)=(1.2.3....8).(9-1-8)
=(1.2.3....8).0
=0
mik chỉ giải được zậy thôi.
t mik nha.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5/9 + 4/9 . 3/7 + 4/9 . 4/7
= 5/9 + 4/9 . (3/7 + 4/7)
= 5/9 + 4/9 . 1
= 5/9 + 4/9
= 1
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) Ta có: \(\frac{8}{40}+\frac{-4}{20}-\frac{3}{5}\)
\(=\frac{1}{5}+\frac{-1}{5}-\frac{3}{5}\)
\(=\frac{-3}{5}\)
b) Ta có: \(\frac{-7}{12}+\frac{-2}{12}-\frac{-3}{36}\)
\(=\frac{-7}{12}+\frac{-2}{12}-\frac{-1}{12}\)
\(=\frac{-9+1}{12}=\frac{-8}{12}=\frac{-2}{3}\)
c) Ta có: \(\left(\frac{1}{6}+\frac{-4}{13}\right)-\left(-\frac{17}{6}-\frac{30}{13}\right)\)
\(=\frac{1}{6}+\frac{-4}{13}+\frac{17}{6}+\frac{30}{13}\)
\(=3+2=5\)
d) Ta có: \(-\frac{-5}{4}+\frac{7}{4}-\frac{-11}{7}+\frac{2}{7}\)
\(=\frac{5}{4}+\frac{7}{4}+\frac{11}{7}+\frac{2}{7}\)
\(=3+\frac{13}{7}=\frac{21}{7}+\frac{13}{7}=\frac{34}{7}\)
e) Ta có: \(-\frac{1}{8}+\frac{-7}{9}+\frac{-7}{8}+\frac{6}{7}+\frac{2}{14}\)
\(=-1+1+\frac{-7}{9}\)
\(=-\frac{7}{9}\)
f) Ta có: \(\frac{-2}{9}-\frac{11}{-9}+\frac{5}{7}-\frac{-6}{-7}\)
\(=\frac{-2-\left(-11\right)}{9}+\frac{5-6}{7}\)
\(=1+\frac{-1}{7}=\frac{7}{7}+\frac{-1}{7}=\frac{6}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(1\frac{5}{7}\)-\(\frac{9}{7}\)*\(\frac{16}{9}\)
=\(\frac{12}{7}\)-\(\frac{16}{7}\)
=\(\frac{-4}{7}\)
b. \(\frac{-5}{8}\):\(\frac{1}{4}\)-\(\frac{6}{13}\)*4+\(\frac{3}{8}\)
=\(\frac{-5}{8}\cdot\)4-\(\frac{6}{13}\)*4+\(\frac{3}{8}\)
=4*(\(\frac{-5}{8}\)-\(\frac{6}{13}\))+\(\frac{3}{8}\)
=4*\(\frac{-113}{104}\)+\(\frac{3}{8}\)
=\(\frac{-113}{26}\)+\(\frac{3}{8}\)
=\(\frac{-413}{104}\)
c.( \(\frac{3}{8}\)+\(\frac{-1}{4}\)-\(\frac{5}{12}\)):\(\frac{1}{3}\)
=\(\frac{-7}{24}\)*3
=\(\frac{-7}{8}\)
Học tốt
a ) 2 5 7 .4 1 5 = 19 7 . 21 5 = 57 5 . b ) 6 5 8 : 2 7 4 = 53 8 : 15 4 = 53 30
c ) 6 7 8 . − 2 14 9 = 55 8 . − 32 9 = − 220 9
d ) 1 7 8 : − 4 1 4 = 15 8 : − 17 4 = − 15 34
e ) − 4 2 9 . − 5 1 2 = − 38 9 . − 11 2 = 209 9 f ) − 2 8 9 : − 4 1 3 = − 26 9 : − 13 3 = 26 39 g ) 3 6 5 .2 = 3 + 6 5 .2 = 3.2 + 6 5 .2 = 6 + 12 5 = 42 5 h ) 5 4 7 : 2 = 5 + 4 7 : 2 = 5 2 + 2 7 = 39 14